Severe Chest Pain in a Young Patient with Behçet’s Disease: A Rare Manifestation - Steen Reed; Michael McGee; Shanathan Sritharan (Case Reports in Cardiology)
A 32-year-old man with a background of Behçet’s disease developed severe chest pain. The onset coincided with an episode of sacroiliitis. The patient was diagnosed with pericarditis and was successfully treated with a combination of anti-inflammatory agents. Pericarditis is a rare manifestation of Behçet’s disease.